A contemporary training concept in critical care cardiology - Binzenhöfer, Leonhard; Gade, Nils Christian; Roden, Daniel; Saleh, Inas; Lanz, Hugo; Sierra, Laura Villegas; Seifert, Paula; Scherer, Clemens Martin; Schrage, Benedikt; Härtel, Franz; Hoyer, Daniel; Preusch, Michael; et al. (Frontiers in Cardiovascular Medicine, 2024)
Critical care cardiology (CCC) in the modern era is shaped by a multitude of innovative treatment options and an increasingly complex, ageing patient population. Generating high-quality evidence for novel interventions and devices in an intensive care setting is exceptionally challenging. As a result, formulating the best possible therapeutic approach continues to rely predominantly on expert opinion and local standard operating procedures. Fostering the full potential of CCC and the maturation of the next generation of decision-makers in this field calls for an updated training concept, that encompasses the extensive knowledge and skills required to care for critically ill cardiac patients while remaining adaptable to the trainee’s individual career planning and existing educational programs. In the present manuscript, we suggest a standardized training phase in preparation of the first ICU rotation, propose a modular CCC core curriculum, and outline how training components could be conceptualized within three sub-specialization tracks for aspiring cardiac intensivists.